Time-resolved Förster-resonance-energy-transfer DNA assay on an active CMOS microarray - Schwartz, David Eric; Gong, Ping; Shepard, Kenneth L. (Biosensors & bioelectronics, 2008)
We present an active oligonucleotide microarray platform for time-resolved Förster-resonance-energy-transfer (TR-FRET) assays. In these assays, immobilized probe is labeled with a donor fluorophore and analyte target is labeled with a fluorescence quencher. Changes in the fluorescence decay lifetime of the donor are measured to determine the extent of hybridization. In this work, we demonstrate that TR-FRET assays have reduced sensitivity to variances in probe surface density compared with standard fluorescence-based microarray assays. Use of an active array substrate, fabricated in a standard complementary metal-oxide-semiconductor (CMOS) process, provides the additional benefits of reduced system complexity and cost. The array consists of 4096 independent single-photon avalanche diode (SPAD) pixel sites and features on-chip time-to-digital conversion. We demonstrate the functionality of our system by measuring a DNA target concentration series using TR-FRET with semiconductor quantum dot donors.